Cryptocurrency Investment and Economic Stability: A Risk Analysis in Emerging Markets - Putri, Ratih Astiakurnia; Marbun, Robert; Harjanti, Wulandari (Yayasan Ilomata, 2025)
The rapid development of cryptocurrency investment has raised concerns regarding its impact on economic stability, particularly in emerging markets. This study employs a qualitative approach through literature review and library research to analyze the risks associated with cryptocurrency investments and their implications for financial stability. This research identifies key risk factors, including market volatility, regulatory uncertainty, cybersecurity threats, and financial system disruptions by examining existing scholarly works, regulatory frameworks, and market trends. The findings indicate that cryptocurrency investments offer opportunities for financial inclusion and economic diversification but also pose significant risks to economic stability due to price fluctuations and speculative behavior. Furthermore, the lack of a unified regulatory framework across different countries exacerbates these risks, leading to potential financial instability in emerging economies. The study highlights the necessity of regulatory intervention and policy formulation to mitigate these risks while harnessing the benefits of cryptocurrency investments. Governments and financial institutions in emerging markets must establish robust risk management strategies and regulatory frameworks to balance innovation and financial stability. This research contributes to the academic discourse by providing a comprehensive understanding of the relationship between cryptocurrency investments and economic stability in emerging markets. Future research should focus on empirical case studies to further explore the long-term effects of cryptocurrency investments on financial stability.